THE IMPACT OF SONGS ON STUDENTS' WRITING SKILLS - Haris, Sahlah; Siswana, Siswana (STKIP Siliwangi, 2024)
This quasi-experimental study examined the effectiveness of using English songs to teach writing skills to tenth-grade students at a Jakarta high school. The study involved 68 students over two classes. One class was given the song-based instruction as the experimental group, while the other class functioned as the control group. Both classes had pre-tests and post-tests to evaluate the impact of the treatment. Using IBM SPSS Statistics, the experimental class improved their average scores by 7.56 points compared to 4.59 points in the control group. The data revealed that the 2-tailed significance is p (0.039), while the alpha significance (α) is 0.05. Thus, since 0.039 is less than 0.05, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. These findings indicate that the use of song into writing class could be a useful method for improving student performance.